2020
DOI: 10.1515/bot-2020-0017
|View full text |Cite
|
Sign up to set email alerts
|

The Ulvophyceae (Chlorophyta) of eastern Sorsogon, Philippines, including Halimeda magnicuneata sp. nov. (Bryopsidales)

Abstract: The marine algal flora of eastern Sorsogon has been intensively collected and is generally considered as the richest in the Philippines. A trend of species records in the area has been dominated by rhodophytes (red algae) with significantly fewer similar studies for other algal groups (green and brown algae). In this study we present an updated catalogue of the green seaweeds (Ulvophyceae) of eastern Sorsogon. A checklist, including notes on taxonomy, is given of the 103 species. Twenty-six species are newly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Mounting evidence has shown those seaweeds in eastern Sorsogon are abundant and diverse, yet those that are regarded as ethnotaxa are not documented. Currently, there are about 250 seaweed species recorded for the area (Trono 1975, 1976, Kraft et al 1999, Dumilag et al 2020. In this study, only 12 species were identified to have ethnobotanical values.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Mounting evidence has shown those seaweeds in eastern Sorsogon are abundant and diverse, yet those that are regarded as ethnotaxa are not documented. Currently, there are about 250 seaweed species recorded for the area (Trono 1975, 1976, Kraft et al 1999, Dumilag et al 2020. In this study, only 12 species were identified to have ethnobotanical values.…”
Section: Discussionmentioning
confidence: 69%
“…Besides being edible, the Philippine C. edule has anti-cancer properties (Bayro et al 2019. Including C. edule, six other Codium species were reported from eastern Sorsogon (Dumilag et al 2020). Codium materials from eastern Sorsogon may also be tested to diversify seaweed species selection for drug discoveries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pickeringii: French Polynesia [12,21,24]. The species was also reported in the Philippines [37] based on field identification but not confirmed genetically. Littler and Littler (2003) have recorded the species in Fiji [38].…”
Section: Taxonomic Treatmentmentioning
confidence: 99%